Design and Build Security for Open and Close System of House Fence Using a Microcontroller-Based Remote Control - Nashrullah Mujibur Rahman; Didik Tristianto; Slamet Winardi (Natural Sciences Engineering and Technology Journal, 2021)
Home security is an inevitable need. The security system on the fence by entering a password on the remote control allows ensuring security. This study aimed to design a security system technology that is automated when the homeowner enters a pre-set password/passcode. All of these systems are connected to the ATmega8535 microcontroller which has been programmed using the Code Vision Avr software stored in the ATmega8535 microcontroller memory and supporting memory as a means of storing password data. In conclusion, the security design of opening and closing the house fence with a remote control based on a microcontroller increases the security of the home environment.